The Effectiveness Of Interactive Learning Media In Early Childhood Education: Evidence From Indonesian Preschools - Uli Mamudho; Umi Sholihatin Nisa (Journal of Global Educational Perspectives, 2026)
This study aims to examine the effectiveness of interactive learning media in early childhood education, with a focus on Indonesian preschools. A quantitative approach with a quasi-experimental design was employed, involving an experimental group and a control group using a pre-test and post-test framework. The participants consisted of children aged 4–6 years selected through purposive sampling. Data were collected using learning outcome tests, observation sheets to measure student engagement, and teacher questionnaires. The results indicate that the experimental group exposed to interactive learning media showed a significantly higher improvement in learning outcomes compared to the control group. In addition, student engagement—including attention, participation, interaction, and enthusiasm—was notably higher in the experimental group. Statistical analysis confirmed that the differences between the two groups were significant at the 0.05 level. The findings suggest that interactive learning media are effective in enhancing both cognitive development and classroom engagement in early childhood education. However, challenges such as limited infrastructure and teacher readiness were also identified. This study highlights the importance of integrating interactive media with appropriate pedagogical strategies and recommends broader implementation supported by adequate training and resources.